Application of paper spray–MS in PK studies using sunitinib and benzethonium as model compounds. (March 2015) - Takyi-Williams, John; Dong, Xueming; Gong, Haiqing; Wang, Yang; Jian, Wenying; Liu, Chuan-Fa; Tang, Kai
Aim: Current bioanalytical methods applied in nonclinical PK studies for screening drug candidates demand significant amount of time and resources, hence, the need to develop alternative methods.Results: A proof-of-concept paper spray–MS method for the detection and quantitation of small molecules in plasma has been developed and validated using sunitinib and benzethonium as model compounds. The method includes single oral or intravenous administration of sunitinib to mice and serial micro-volume (20 µl) blood collection at different time intervals. The method is rapid with overall analysis time of 1 min and a full PK profile of sunitinib was obtained from a single mouse.Conclusion: The paper spray–MS approach is simple, sensitive and can potentially enable significant reduction of animal use and cost.